Divadlo bez domova - Richards, Benjamin (Australia : Apothecary Films)
Divadlo bez Domova (Theatre With No Home), founded in 2006, is an organization working with homeless people, as well as socially, physically or emotionally handicapped. The project is run by Patrik Krebs, his wife Ursula and many passionate people in Bratislava, Slovakia. Their main goal is to develop and perform their own theatre performances and create interaction between human beings who live on the outskirts of society to discover and show their talents.
Verzio Film Festival Submission
Duration: 00:52:00
Verzio Film Festival Submission
Keywords: Documentary films